ENHANCEMENT OF PIXEL VALUE ORDERING BASED DATA HIDING BY ROW BLOCK PARTITION - Hendro Eko Prabowo; Tohari Ahmad (Jurnal Ilmu Komputer dan Informasi, 2018)
The development of information and communication technology that support digital data transmission such as text, image, audio and video gives several effects. One of them is data security that becomes the main priority during the transmission process. Pixel-Value-Ordering (PVO) which one of data hiding methods can be implemented to achieve the requirement. It embeds data on maximum pixel and minimum pixel in a blok which is a part of the carrier image. However, PVO has capacity a problem, that only 2 bits per block can be hidden. To handle this problem, we propose a new approach by dividing blocks dinamically based on its complexity. These blocks are grouped into 4: smooth block, semi-smooth block, normal block and rough block. Using this approach, the stego capacity can be improved up to 2.6 times in average of  previous method by keeping the quality stego more than 65 dB for all testing image.